Fiscal Decentralisation and Economic Growth in Indonesia - Cahyadi, Erdhany Dwi (Badan Penerbitan Jurnal (BPJ) FIA-UB, 2019)
Fiscal decentralisation is deemed as an effective policy to increase efficiency in providing public goods and appears as a way to foster economic growth. This paper addresses the theoretical and empirical linkage between fiscal decentralisation on economic growth. Here, we use five decentralisation measures to capture the multidimensional aspect of fiscal decentralisation. Using data from the lowest level of government and the latest data in Indonesia from 2010 to 2017, the results showed that fiscal decentralisation is significantly and negatively related to economic growth.